Exploring Sociosexuality: The Role of Dark Tetrad in Predicting Casual Sex Attitudes among Indonesian Adults - Herwandha, Karenina Graceilia; Masykuroh, Maryam Abidah; Asih, Sali Rahadi (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Attitude toward casual sex can lead to various risky behaviors and therefore, needs to be further explored. This study was conducted in Indonesia, where religious and social norms are strongly against premarital sex, so the findings on the role of the Dark Tetrad may differ from the Western context. This study examined the role of the dark tetrad personality in predicting attitudes toward casual sex among 733 adults in Indonesia (Mage = 28.7, SD = 5.47, 50.1% male; 59.8% married), controlling for demographic factors (i.e., age, biological sex, and marital status). Hierarchical regression analysis revealed that psychopathy (β = 0.160) and sadism (β = 0.175) showed small to moderate effects in predicting permissive attitudes, accounting for an additional 7.9% variance after controlling for demographic factors. These findings highlight the psychological dimensions of permissive attitudes toward casual sex and demonstrate that dark personality traits have stronger predictive roles than demographic factors.  Keywords: attitude toward casual sex, dark tetrad, trait sadism, trait psychopathy, gender, marital status